Predictor of Stunting Among Children 0-24 Months Old in Indonesia: A Scoping Review - Via Eliadora Togatorop; Laili Rahayuwati; Raini Diah Susanti (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Stunting, a condition of impaired growth and development due to chronic malnutrition, remains a significant challenge in Indonesia. Efforts to address this issue have been hindered by an inadequate understanding of the predictors of stunting, particularly in the first 1000 days of a child's life. To address this gap, a scoping review was conducted to identify factors influencing stunting in children aged 0-24 months in Indonesia. The review focused on observational studies published from 2012 to 2023, retrieved from five international databases using specific keywords. Among the 16 articles, 10 factors with 26 predictors emerged, spanning child, mother, home, inadequate complementary feeding, inadequate breastfeeding, poor quality foods, infection, political economy, health and healthcare, and social culture factor. Most predictors aligned with mother, child, and home factors. These findings provide a foundation for targeted interventions and collaborative efforts across sectors to combat stunting and ensure healthier futures for Indonesia's children.